The Maximal "Kinematical" Invariance Group for an Arbitrary Potential Revised - Nikitin, A.G. (Журнал математической физики, анализа, геометрии, 2018)
Group classification of one particle Schrödinger equations with arbitrary potentials (C.P. Boyer, Helv. Phys. Acta 47 (1974), p. 450) is revised. The corrected completed list of non-equivalent potentials and the corresponding symmetries is presented together with exact identification of symmetry algebras and admissible equivalence transformations. Переглянуто групову класифiкацiю одночастинкового рiвняння Шредiнгера з довiльним потенцiалом (C.P. Boyer, Helv. Phys. Acta 47 (1974), p. 450). Представлено виправлений перелiк нееквiвалентних потенцiалiв та вiдповiдних симетрiй разом з точною iдентифiкацi№ю алгебр симетрiй та допустимих перетворень еквiвалентностi.